The Implicature of Foreign Speakers in Instagram Content - Habibi, Ahmad Fajar; Zulaeha, Ida; Mardikantoro, Hari Bakti (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Instagram video content that contains speech is included in a new pattern of social media interaction. As a part of the pattern of social interaction, speech in Instagram video content needs to be analyzed for its implications. The purpose of this study was to find out the implicatures in Indonesian-language content made by foreign speakers on social media of Instragram. The content of Indonesian speech made by foreign speakers is quite varied, such as comedy content, culinary arts, family life, and other social activities. Some of the social media contents of foreign speakers that currently available has a tendency to not consider the moral burden of using Indonesian speech. This tendency appears as an implicature concept that needs to be investigated at the pragmatic level of Indonesian speech. This study used two approaches, those were a theoretical approach and a methodological approach. The theoretical approach chosen was a pragmatic theory approach to analyze speech implicatures using Grice's theory. The methodological approach used in this research was a qualitative research method with a descriptive approach. The results of this study were implicatures of five utterances from four foreign speakers who had different characteristics of the Instagram video content they made. The implicatures contained in the five utterances were 3 in the conventional implicature category, 2 in the unconventional implicature category, and 1 in the presuppositional implicature category.